Impregnation Nickel on Mesoporous ZSM-5 Templated Carbons as a Candidate Material for Hydrogen Storage - Ratna Ediati; Amirul Mukminin; Nurul Widiastuti (Universitas Gadjah Mada, 2017)
A series of carbon with ZSM-5 mesoporous (ZMC) and Ni/ZMC ZSM-5 templates were synthesized and gravimetrically known its adsorption capacity to H2 gases. ZMC carbon was synthesized using a hard template method at a carbonation temperature of 900 oC with sucrose as a source of carbon. A mesoporous ZSM-5 template was synthesized by using a hydrothermal method at an aging and crystallization temperature of respectively 60oC and 150oC for as long as 24 hours. The characterized result of ZMC carbon using XRD powder has shown a diffracted pattern of amorphous carbon. Impregnating Ni with ZMC carbon each resulted in 5%, 15% and 25% of weight, which in turn also resulted in a diffractogram pattern of Ni/ZMC-5, Ni/ZMC-15, and Ni/ZMC-25, where each patterns were uniform and had no additional peaks. The results of SEM-EDAX showed that Ni had been successfully impregnated on the surface of ZMC carbon with a random morphology surface of ZMC carbon. The isothermal results of adsorption – desorption of N2 showed that the larger the Ni loading on the supporting ZMC carbon, the smaller the surface area of the ZMC specific carbon. The distribution of the pore size that was counted by using the BJH method, which was applied to all the samples, was as big as 3,8 nm. The adsorption capacity of H2 was measured by using the gravimetry method at ambient temperature for Ni/ZMC-5, Ni/ZMC-15, and Ni/ZMC-25, which each gave a weight percentage of 0,331%; 0,663% and 0,649% respectively, whilst the ZMC carbon has a weight of 2,18%.